Exploring the Core Formose Cycle: Catalysis and Competition - Jeremy Kua; L. Philip Tripoli (Life, 2024)
The core autocatalytic cycle of the formose reaction may be enhanced or eroded by the presence of simple molecules at life’s origin. Utilizing quantum chemistry, we calculate the thermodynamics and kinetics of reactions both within the core cycle and those that deplete the reactants and intermediates, such as the Cannizzaro reaction. We find that via disproportionation of aldehydes into carboxylic acids and alcohols, the Cannizzaro reaction furnishes simple catalysts for a variety of reactions. We also find that ammonia can catalyze both in-cycle and Cannizzaro reactions while hydrogen sulfide does not; both, however, play a role in sequestering reactants and intermediates in the web of potential reactions.